Developing A Digital Fundraising Web Platform to Enhance Social Impact Outcomes - Magdalena, Lena; Febima, Mesi; Hatta, Muhammad; Asfi, Marsani; Solihin, Unang; Umar Fachrudin, Mochammad (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
The rapid advancement of digital technology has transformed fundraising practices by enabling wider outreach, improved transparency, and enhanced efficiency; however, many social impact programs continue to face challenges related to donor engagement, fund management, and accountability. This study focuses on the implementation of a digital fundraising web system aimed at enhancing social impact outcomes through optimized fundraising processes and strengthened stakeholder interaction. The system was developed using a web-based architecture and designed following the System Development Life Cycle (SDLC), encompassing requirement analysis, system design, implementation, and testing phases. Key features include donor registration, campaign management, secure online donation processing, real-time monitoring, and reporting dashboards that allow donors and administrators to track fund utilization transparently. System evaluation was conducted through functional testing and user acceptance testing involving system administrators and donors to assess usability, performance, and reliability. The results indicate that the implemented system improves operational efficiency, minimizes manual errors, and increases transparency in fundraising activities, which in turn enhances donor trust and participation. Moreover, the platform supports more effective allocation of funds toward social programs, contributing to measurable improvements in social impact outcomes. This research demonstrates that the adoption of a digital fundraising web system can serve as a strategic tool for social organizations to leverage information technology in achieving sustainable social impact. The study contributes to the multidisciplinary discourse on digital innovation and social entrepreneurship by providing an applicable model for technology-driven fundraising systems, while future research may explore the integration of advanced data analytics, mobile platforms, and artificial intelligence to further optimize donor engagement and impact assessment.